Estrat??gia de megaevento esportivo: impactos e legados do GP Brasil de F??rmula 1 para a cidade de S??o Paulo - Varotti, Felipe de Pilla (2016)
Sports mega-events are increasingly being adopted by government entities as a strategy to project an image of the country and generate a significant international exposure, indicating the development of a particular city or country. Sports mega-events are correlated to the major international competitions, with high media coverage by different countries and large capital investment that attracts a large number of visitors and are organized by governmental and non-governmental entities such as the F1 GP Brazil. This event was used by governors of the city of S??o Paulo as a strategic focus, aiming an international exhibition and economic development. Thus, the main objective of this study was to evaluate the impacts and the legacies triggered by this event in S??o Paulo city. Adopting a descriptive and exploratory research, by a qualitative method, municipal managers, event organizers and local population were interviewed. It was possible to establish that the event generates some impacts, such as: economic, infrastructure, socio-cultural, psychological and administrative. In large part, externalities, as the results of certain activities. As legacies, improvements have been identified in the infrastructure and new public facilities, knowledge and skills developed by the organizers and managers involved in the event, international exposure, improving the city's reputation, establishment of a network, legacies related to motor racing history and the automotive industry, and sports legacy. The contributions of this research refer to the management of sport insofar as it demonstrated that the impacts and legacies are generated taking into consideration a series of cultural, historical, economic factors, in addition to the characteristics and resources of the host city. Indeed, it was possible to demonstrate that events held annually in one place have peculiar characteristics that favor the identification with their host cities, unlike those itinerant mega-events, performed every four years in different places. This study opens perspectives for public managers aiming at better strategic planning before proposing the accomplishment of events of this magnitude. Thus, it becomes possible to develop a sustainable sport mega event that can offer the positive impacts, both for its participants, but mainly for those who inherit the legacy of these events.